ANALYSIS OF PATIENT’S EXPECTATION AND SATISFACTION IN THE CLINIC FOR ASTHMA-ALLERGY OF DR. INDRAJANA JAKARTA - Hartono, Budi; Yusta, Theresa (Journal of Ultimate Public Health, 2017)
Background: Today, Community healthcare requires provider’s reliability in order to satisfy the patient. The healthcare provider should be able to measure the level of performance and the level of importance in order to service efficiency.Method: The research used quantitative method with operational research design to measure importance level and performance of service attribute in poly Asma-Allergy Dr. Indrajana Clinic Jakarta. Level of importance and performance measured by Importance-Performance Analysis (IPA) method to 20 types of service attributes, Patient expectation describes Importance level, while patient satisfaction describes Performance level of service attribute.Results: The results showed that there are 10 types of service attributes that should be "Maintained", one type of service attribute should be "Fixed", one type of service attribute should be "Low Priority", and 8 types of service attributes should be "Eliminated". The average fit between satisfaction with expectation is 82.46%. The middle value of importance level is 4,19 and performance 3,67 (on scale 1 until 5).Conclusion: This study found that the level of compliance between patient satisfactions with patient expectation is not yet optimal. Clinics have quite a number of service attributes that are superior, but there are still service attributes that must be improved and should even be ruled out. It is suggested to the Clinical management to optimize service resources on attributes that should be "Maintained".